Chronology and documentary handbook of the State of North Dakota - Vexler, Robert I. (Dobbs Ferry, N.Y. : Oceana Publications, 1978)
A chronology of historical events of the state of North Dakota from 1450 to 1977 with a biographical directory of prominent citizens and copies of pertinent documents.
Cover title: North Dakota, a chronology & document handbook.
Bibliography: p. 145. and index.
Keywords: North Dakota -- History -- Chronology; North Dakota -- Biography; North Dakota -- History -- Sources; North Dakota -- History